Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.4161/cbt.3.4.779
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Progression of Microvasculature in Primary Tumor and Lymph Node Metastases in a Breast Carcinoma Model: Relationship between Microvessel Density, Vascular Endothelial Growth Factor Expression and Metastatic Invasion

Abstract: The natural course of tumor microvascularity in rat MTLn3 mammary adenocarcinomas was studied. The relationship between microvessel density (MVD), vascular endothelial growth factor (VEGF) expression, and histopathology was compared in primary and metastatic axillary (ALN) and inguinal lymph node (ILN) tumors over 5-6 tumor doublings. Excised tumors were examined for (i) MVD assessed by immunostaining with anti-CD31 antibody, (ii) VEGF expression assessed by immunostaining with anti-VEGF antibody, and (iii) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…Via its binding to tyrosine kinase receptors, particularly VEGFR-2, VEGF induces mitogenesis and chemotaxis of endothelial cells, which lead to new blood vessel formation, tumor growth, and metastasis. In addition to their typical expression on endothelial cells, VEGF and VEGFR-2 are expressed in certain solid tumors [5,6]. This finding has led to the hypothesis that an autocrine loop exists by which VEGF stimulates tumor growth not only via its actions on endothelial cells but also by directly stimulating VEGFR-2 on tumor cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Via its binding to tyrosine kinase receptors, particularly VEGFR-2, VEGF induces mitogenesis and chemotaxis of endothelial cells, which lead to new blood vessel formation, tumor growth, and metastasis. In addition to their typical expression on endothelial cells, VEGF and VEGFR-2 are expressed in certain solid tumors [5,6]. This finding has led to the hypothesis that an autocrine loop exists by which VEGF stimulates tumor growth not only via its actions on endothelial cells but also by directly stimulating VEGFR-2 on tumor cells.…”
Section: Discussionmentioning
confidence: 97%
“…Evidences support the correlation between levels of VEGF tumor progression and invasion in breast cancer, which is the leading cause of death in women 30 to 70 years of age in the world [5,8,9]. VEGFR-2 and VEGF are coexpressed in primary breast carcinomas, and their expression is increased when tumors shift to an angiogenic phenotype [10].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…High levels of angiogenic factors and histologic evidence of increased tumour neovascularization are considered to be associated with malignancy and prognosis in human breast cancer (Hanahan and Folkman, 1996;Locopo et al, 1998;Gasparini, 2000Gasparini, , 2001Leek, 2001) and different studies have indicated similar results in CMT (Restucci et al, 2000;Lavalle et al, 2009;Queiroga et al, 2011). EGFR signaling and angiogenesis have been independently evaluated as targets for therapy in human studies (Fox et al, 1994;Weidner and Gasparini, 1994;Nieto et al, 2007;Nickerson et al, 2012) and several factors support the potential interaction between them: tumour cells can be stimulated in a paracrine manner by growth factors; endothelial cells and tumour cells can stimulate each other's growth in the tumour microenvironment (Rowe et al, 2004); both EGF and TGF-a (ligands for EGFR) induce angiogenesis (Perrotte et al, 1999); EGFR expression and function in tumour-associated endothelial cells have also been described (Rak et al, 1995).…”
Section: Introductionmentioning
confidence: 88%
“…[11][12][13] Expression of VEGF and its receptors (VEGFR-2 and VEGFR-3) have extensively been correlated with malignant behavior, metastasis, and worsened prognosis in many different tumor types including colorectal cancer, prostate cancer, head and neck squamous cell cancer, breast cancer, ovarian cancer, and lung cancer. [14][15][16][17][18][19] In addition, anti-VEGF receptor antibodies have been demonstrated to decrease tumor growth, decrease angiogenesis, and increase hypoxia in preclinical studies. 20,21 Clinically, they also have been shown to increase patient survival when combined with chemotherapy.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%